Distingsi Hadis Bid’ah Perspektif Muhammadiyah dan Wahabi-Salafi - Sarwan Sarwan; Muhammad Sabri (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
Muhammadiyah and Wahabi groups are revivalist Islamic movements, which in their struggle are both against heresy, so that their similarities make them look the same, some even say that Muhammadiyah is part of Wahhabism. then what is the difference in understanding heresy in the view of Muhammadiyah and Wahhabis. The methodology used in this research is Qualitative (Library research). Literature research that uses a comparative approach. By collecting all the materials for books, journals, reference papers related to the understanding of Muhammadiyah and Wahhabism about the heretical hadith. Then the data is reviewed, criticized, analyzed critically and comparatively, then a conclusion is drawn. As for the findings; First, in Muhammadiyah's understanding of the hadith, bid'ah is divided into two, namely hasanah bid'ah and dhalalah bid'ah, while according to Wahhabis all bid'ah is dhalalah. Second, Wahhabis consider relying on dhaif hadith as a heretical heresy, while Muhammadiyah allows apologies to motivate worship. Third, regarding tawassul, Wahhabis do not justify tawassul to pious people, whether living or dead, in contrast to Muhammadiyah which allows tawassul to pious people who are still alive, and not to the dead.